2013
DOI: 10.1038/oncsis.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of radiation-induced DNA double-strand break repair by MyD88 is accompanied by apoptosis and crypt loss in mouse colon

Abstract: Intestinal microbes promote the injurious effects of radiation on those tissues. However, the molecular factors mediating this effect are largely unknown. In this work, we explored the effects of orally administered antibiotics and MyD88, a key adapter molecule in toll-like receptor signaling, on molecular and cellular responses of mouse colon to radiation. Results show that oral antibiotics lowered radiation-induced colonic damage by protecting epithelial cells against radiation-induced apoptosis, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
11
1
1
Order By: Relevance
“…In the present study, we investigated the radiation susceptibilities of TLR-knockout mice to evaluate the impact of TLR deficiency on GIS. A recent study has suggested that Myd88 − / − mice showed marked resistance to GIS35. However, our study revealed that there was no attenuation of GIS in mice deficient in TLR2, 4, 5, 7 and 9.…”
Section: Discussioncontrasting
confidence: 75%
“…In the present study, we investigated the radiation susceptibilities of TLR-knockout mice to evaluate the impact of TLR deficiency on GIS. A recent study has suggested that Myd88 − / − mice showed marked resistance to GIS35. However, our study revealed that there was no attenuation of GIS in mice deficient in TLR2, 4, 5, 7 and 9.…”
Section: Discussioncontrasting
confidence: 75%
“…Tissue sections (5-micron) were cut, deparaffinised, rehydrated, and stained with hematoxylin and Eosin (H and E) staining and stained sections were washed and mounted under a coverslip and examined under light microscopy (Zeiss). The crypt survival assays (Lai and Egan, 2013) were employed to evaluate the radio-sensitivity of the colon post whole-body γ-irradiation in mice.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of TLR4, and its co‐receptors CD14 and MD‐2, with LPS results in recruitment of the adapter molecule myeloid differentiation marker 88 (MyD88), phosphorylation of IL‐1 receptor associated kinase and recruitment of the adapter molecule tumor necrosis factor receptor‐associated factor (TRAF)−6 . Recent research has attempted to delineate the mechanisms by which TLR4 contributes to gastrointestinal immunity by altering intestinal microbes and MyD88 expression . Using a preclinical model, Lai et al .…”
Section: Tlr4/pkc Signallingmentioning
confidence: 99%
“…[108][109][110] Recent research has attempted to delineate the mechanisms by which TLR4 contributes to gastrointestinal immunity by altering intestinal microbes and MyD88 expression. 111 Using a preclinical model, Lai et al administered a broad-spectrum oral antibiotic to animals treated with 14Gy of whole body irradiation. Antibiotic administration attenuated weight loss, and increased food and water intake.…”
Section: Tlr4/pkc Signallingmentioning
confidence: 99%